MALAM BAINAI DI DAERAH PARAKLAWEH KECAMATAN LUBUK BEGALUNG, KOTA PADANG - Nadya Olivia Perrina (Pendidikan IPA, FMIPA, UNP, 2022)
This article aims to describe about malam banai. Malam bainai is one of the important series in thepreparation for the wedding of the Minangkabau community in the city of Padang with the core of theevent, which is to redden the fingers of the prospective bride with a collision of henna leaves calledLawsonia inermis. The philosophy is to protect the prospective bride from all events that can disturb hersmooth running. the journey of the events to be carried out, both those imported by envious humans andby demons. There was a belief of old people, evil desires from someone can be input through thefingertips. Therefore the fingertips must be protected in red. In placing the henna on the finger, there isthe meaning of each finger that is attached to the henna. Lawsonia inermis L. leaves are effective againstvarious bacteria and have anti-inflammatory, analgesic, and antipyretic effects, so they are widely usedfor medicinal purposes.